Optimization of the extraction of antioxidants from stinging nettle leaf using response surface methodology - Una-Jovana Vajic; Jelena Zivkovic; Milan Ivanov; Djurdjica Jovovic; Katarina Savikin; Branko Bugarski; Nevena Mihailovic-Stanojevic (Macedonian Journal of Chemistry and Chemical Engineering, 2022)
The aim of this study was to optimize the parameters of the extraction of total flavonoids from stinging nettle leaf. Comparison of the effects of different solvents on total flavonoid content showed that, regardless of extraction time, aqueous-methanolic extracts had higher total flavonoid content than aqueous-ethanolic extracts. So, full factorial design and response surface methodology (RSM) were employed to estimate the effects of methanol content (50, 75, and 100 %) and extraction time (30, 60, and 90 minutes) on total flavonoid content and antioxidant capacities of the extracts. RSM analysis showed that methanol content in the solvent influenced significantly total flavonoid content and FRAP (Ferric Reducing Antioxidant Power Assay) antioxidant capacity, while extraction time had no significant effect on either of the responses. Extraction parameters for maximal total flavonoid content were estimated to be 69 % aqueous-methanol and 67 min, and 65 % aqueous-methanol and 83 min for maximal FRAP antioxidant capacity. DPPH (2,2-diphenyl-1-picrylhydrazyl) antioxidant capacity was not significantly affected by extraction time or methanol percentage in the solvent.